Comparative Effects of Stimulant and Antipsychotic Medications on Eating Behaviors and Weight in Children with Attention Deficit Hyperactivity Disorder - Hasan Cem Aykutlu; Esra Okyar; Mehmet Karadağ; Masum Öztürk (MDPI AG, 2024)
Background/Objectives: Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with an increased risk of obesity and disordered eating behaviors. This study compared weight status and eating behaviors among drug-naïve ADHD children, those on stimulant monotherapy, those on combined stimulant and antipsychotic treatment, and healthy controls. Methods: This cross-sectional study included 547 children aged 6-12 years from four Turkish provinces: 361 with ADHD (152 drug-naïve, 156 on stimulants, and 53 on combined therapy), and 186 healthy controls. Anthropometric measurements, psychiatric assessments, and eating behavior evaluations were conducted using standardized tools. Results: Drug-naïve ADHD children had the highest obesity rate (13.8%), while those on stimulant monotherapy had the lowest (4.5%) compared to controls. Combined treatment group obesity rates were similar to controls (7.5% vs. 8.6%). The drug-naïve and combined treatment groups showed increased food approach behavior and desire to drink, with the combined treatment group also showing increased emotional overeating. Conclusions: This study reveals a complex relationship between ADHD, its pharmacological management, and the risk of obesity. Stimulant monotherapy may mitigate the risk of obesity, while combined stimulant and antipsychotic treatment may lead to problematic eating behaviors. These findings emphasize the importance of monitoring weight status and eating behaviors in ADHD children, especially those receiving pharmacological interventions.